Micropore Structural Characteristics and Influence Factors of Triassic Shale Gas Adsorption in the Ordos Basin - Yang, Fu; Ma, Dongmin; Duan, Zhonghui; Ren, Dazhong; Tian, Tao; Fu, Deliang (Frontiers in Physics, 2022)
Continental shale is investigated for potential terrestrial shale gas reservoirs in the Tongchuan area, southern Ordos Basin. The kerogen macerals of Upper Triassic Chang 7 shale are vitrinite 28 43%, exinite 4 7%, and inertinite 52 69% and Ro is 0.85 0.88% and the kerogen type is II. The total organic carbon (TOC) content is 9.75 29.92%, free hydrocarbon (S1) is 3.21 12.14%, pyrolysis hydrocarbon(S2) is 41.86 165.39%, and maximum pyrolysis temperature (Tmax) is 439 445℃. The mineral composition is mainly quartz 3.94 43.27%, followed by feldspar 9.65 30.07% and clay minerals 13.46 59%. illonite/smectites (I/S) is the main clay mineral, accounting for 47 69%. The liquid nitrogen adsorption curve showed that the pore types were tubular and plate-like. The pores are mainly micropores (<2nm) and mesoporous (2 50nm). Isothermal adsorption results show that langmuir volume (VL) is 2.06 5.57 cm3·g-1, langmuir pressure (PL) is 2.16 3.28 MPa, and shale adsorption capacity is small and easy to desorption. A quartz content less than 25% is negatively correlated with specific surface area (SSA); otherwise it is positively correlated. A clay mineral content less than 45% is negatively correlated with SSA; otherwise it is positively correlated. The relationship of carbonate content and pore structure are not obvious. Pyrite content less than 2% is positively correlated with SSA, otherwise it is negatively correlated. The SSA is positively correlated with TOC, inertinite and exinite, and negatively correlated with vitrinite. The adsorbed gas content is positively correlated with TOC content, SSA, inertinite content and exinite content, and negatively correlated with vitrinite.